Isotropic Robertson-Walker model universe with dynamical cosmological parameter Λ in Brans-Dicke Theory of Gravitation - Singh, Kangujam Priyokumar; Dewri, Mukunda (Communications in Physics, 2016)
This paper discusses about Robertson-Walker space-time with quadratic equation of state and dynamical cosmological parameter Λ . Some exact solutions of Einstein’s field equations for three cases have been obtained. Physical behaviors of the models are discussed in detail.